2005
DOI: 10.1007/s00455-004-0021-6
|View full text |Cite
|
Sign up to set email alerts
|

Findings of Videofluoroscopic Swallowing Studies AreAssociated with Tube Feeding Dependency at Discharge in StrokePatients with Dysphagia

Abstract: The factors associated with tube feeding dependency in stroke patients with dysphagia have received little attention. This study aimed to identify factors independently associated with tube feeding dependency at discharge in stroke patients with dysphagia using videofluoroscopic swallowing studies (VSS) and clinical findings. One hundred eighty-one consecutive tube-fed inpatients with stroke-related dysphagia referred for VSS were enrolled in the study. Of them, 47 patients continued to require tube feeding at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
13
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 35 publications
7
13
1
Order By: Relevance
“…We also noted that the weaned group was younger than the nonweaned group; however, this difference was not strong enough to achieve statistical significance. In contrast to previous studies [ 8 ], no significant association was observed between prior stroke and nasogastric tube removal ( P value = 0.55); however, functional status before this stroke was statistically different ( P value = 0.03).…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…We also noted that the weaned group was younger than the nonweaned group; however, this difference was not strong enough to achieve statistical significance. In contrast to previous studies [ 8 ], no significant association was observed between prior stroke and nasogastric tube removal ( P value = 0.55); however, functional status before this stroke was statistically different ( P value = 0.03).…”
Section: Discussioncontrasting
confidence: 99%
“…In our study, the rate of nasogastric tube removal was 45.8%. This finding is in agreement with those of other studies, in which the weaned rate was 31–74% [ 1 , 8 – 10 ]. Previous studies have reported that younger patients were more likely to have tube feeding removed before discharge compared with older patients [ 1 , 9 ].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Ickenstein et al (8) found that one-third of patients (31.2%; 24/77) underwent PEG removal before discharge and resumed oral diets. Lin et al (9) reported that 25.9% of the 181 patients with stroke underwent PEG removal at discharge. Kim et al's study (10) provided promising results.…”
mentioning
confidence: 99%